1999
DOI: 10.1002/(sici)1097-4636(199908)46:2<253::aid-jbm15>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Bone defect healing enhanced by ultrasound stimulation: Anin vitro tissue culture model

Abstract: Ultrasound has many medical applications. Previous animal and clinical studies have clearly shown a positive effect of ultrasound on the rate of osseous repair. The present in vitro study was designed to elucidate the specific response of bony tissue to ultrasound treatment. Bilateral femora were obtained from 36 mature male Wistar rats. A bone defect was created at the center of each distal metaphysis. The femora were maintained for either 7 or 14 days in in vitro tissue culture and received 15 min of ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 30 publications
1
0
0
2
Order By: Relevance
“…Takikawa et al (12) observed in an experimental study that, after six weeks of US treatment, it had significantly increased the consolidation rate in fractures with bone nonunion, compared with the control group. The same results were found by Sun et al (14) and Lirani et al (15) .…”
Section: Introductionsupporting
confidence: 88%
“…Takikawa et al (12) observed in an experimental study that, after six weeks of US treatment, it had significantly increased the consolidation rate in fractures with bone nonunion, compared with the control group. The same results were found by Sun et al (14) and Lirani et al (15) .…”
Section: Introductionsupporting
confidence: 88%
“…In vitro olarak yapılmış olan çalışmalarda, ultrason tedavisinin osteojenik hücreler üzerinde mekanik stres oluşturarak proliferasyonu ve osteoblastik aktiviteyi uyardığı gösterilmiştir. 28,35,37,38 Dyson ve Brookes 39 sıçanlar üzerinden uyguladıkları 500 mW/cm2'lik ultrason stimülasyonu ile bilateral fibular fraktürlerini incelemişler; ultrasonun özellikle fraktürün erken safhalarında etkili olduğu bulgusuna ulaşmışlardır. Ding ve ark.…”
Section: Introductionunclassified
“…Μεταξύ αυτών αναφέρονται η εφαρμογή ηλεκτρικών ερεθισμάτων, ηλεκτρομαγνητικών πεδίων, υπερήχων, 128,129 το υπερβαρικό οξυγόνο και η χρήση οστικών αλλομοσχευμάτων. 130,131,132,133,44,134,135 Είναι σαφές, ότι είναι δύσκολος ο έλεγχος της θετικής ή της αρνητικής επίδρασης στην πώρωση κατά την εξέλιξή της.…”
Section: άλλοι παράγοντες που επηρεάζουν την πώρωσηunclassified